No is not enough : resisting Trump's shock politics and winning the world we need - Klein, Naomi, 1970- (2017)
"Remember when it all seemed to be getting better? Before Trump happened? What went wrong, and what can we do about it? Naomi Klein - scourge of brand bullies, disaster capitalists and climate liars - shows us how we got to this surreal and dangerous place, how to stop it getting worse and how, if we keep our heads, we can seize the opportunity to make it better. She reveals how Trump is not a freakish aberration, but an extension of the most powerful trends of the last century: celebrity and CEO-worship, Vegas and Guantanamo, soft porn and hard power, fake news and vulture bankers, all rolled into one. His election was not a peaceful transit but a corporate takeover, by people who've knowingly harmed people, societies and our planet. Now their deliberate shock tactics are generating wave after wave of crises, designed to disorientate us and stop us fighting back. This book is the toolkit for shock resistance, giving all of us what we need (including tips such as 'how to jam the brand' and 'kill your inner Trump') to win the argument and right their wrongs. Don't let them get away with it."--
Part I. How we got here: rise of the superbrands -- How Trump won by becoming the ultimate brand -- The first family of brands -- The Mar-a-Lago hunger games -- Part II. Where we are now: climate of inequality -- The climate clock strikes midnight -- The grabber-in-chief -- Politics hates a vacuum -- Learn to love economic populism -- Part III. How it could get worse: the shocks to come -- Masters of disaster: doing an end run around democracy -- The toxic to-do list: what to expect when you are expecting a crisis -- Part IV. How things could get better -- When the shock doctrine backfires -- When no was not enough -- Lessons from Standing Rock: daring to dream -- A time to leap: because small steps won't cut it -- Conclusion. The caring majority within reach -- Postscript: The leap manifesto.
Keywords: Civil disobedience -- United States; Political culture -- United States; Political participation -- United States; Political psychology -- United States; Political sociology; Government, Resistance to -- United States; United States -- Politics and government -- 2009-2017.